Measuring health-related quality of life of intellectually disabled children: a narrative review - Sasinthar, Karthikayini; Boratne, Abhijit V.; Sugumaran, Arun; Patil, Raj Kumar (International Journal Of Community Medicine And Public Health, 2021)
To identify currently available measures of Health-related quality of life (HRQOL) for intellectually disabled children and to describe their content. A comprehensive retrieval of the English literature from 2001 to 2021 was done in the PubMed and Google Scholar. The terms ‘Intellectual disability’, ‘Differently abled’, ‘Special children’, ‘Differently challenged’, ‘Mental retardation’, ‘Health-related quality of life’, ‘Quality of life’, ‘Burden of intellectual disability’ and ‘India’ were used to identify measures of HRQOL for children’s with intellectual disability. Several tools were identified to measure HRQOL for children with intellectual disability. Many have parent proxy as well as self-report form with good validity and reliability. Though, they were often developed with minimal involvement from families, focus on functioning rather than wellbeing, and have items that sometimes may cause emotional upset. When children with different health problems are compared, the degree of their particular health condition should be measured. Furthermore, overlap of items seems not to be a problem when the HRQOL of children with intellectually disability is studied. Hence, HRQOL assessments are useful for collecting information beyond the clinical symptoms of a health problem thus improving quality of care.